2012
DOI: 10.1037/a0029420
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of career satisfaction among practicing psychologists.

Abstract: Are psychologists satisfied with their careers? The present study sought to answer this question and to understand factors that relate to high levels of career satisfaction. Data from 595 respondents of a national survey of practicing psychologists indicated that, consistent with past research, psychologists tend to be satisfied with their careers. To investigate factors that predict high levels of satisfaction, two groups of psychologists were identified: a high-satisfaction group (n = 129) and a moderate-sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Nevertheless, the findings of these two studies, with both pointing toward concepts of financial security and a sense of control over work-life balance, may help us understand why our neuropsychology data-set, as evident in Table 12, appears to show work-life balance ratings that are relatively independent of ratings of income. What is less clear is why in Table 13 gender appears to be the only variable that has a consistent relationship to all types of career satisfaction, a finding that might not be expected based on the Rupert et al (2012) or the Leigh et al (2009) career satisfaction studies. It might be advisable in future surveying of neuropsychologists to ask for an overall rating of career satisfaction, separately from income, job, and work-life balance satisfactions, in order to better investigate the presumably complex relationships between types of satisfaction and important professional variables relevant to clinical neuropsychologists.…”
Section: Understanding Various Types Of Career Satisfaction: Context mentioning
confidence: 68%
See 1 more Smart Citation
“…Nevertheless, the findings of these two studies, with both pointing toward concepts of financial security and a sense of control over work-life balance, may help us understand why our neuropsychology data-set, as evident in Table 12, appears to show work-life balance ratings that are relatively independent of ratings of income. What is less clear is why in Table 13 gender appears to be the only variable that has a consistent relationship to all types of career satisfaction, a finding that might not be expected based on the Rupert et al (2012) or the Leigh et al (2009) career satisfaction studies. It might be advisable in future surveying of neuropsychologists to ask for an overall rating of career satisfaction, separately from income, job, and work-life balance satisfactions, in order to better investigate the presumably complex relationships between types of satisfaction and important professional variables relevant to clinical neuropsychologists.…”
Section: Understanding Various Types Of Career Satisfaction: Context mentioning
confidence: 68%
“…An excellent example is provided by Rupert, Miller, Tuminello Hartman, and Bryant (2012), who used optimal discriminant analysis to identify factors that might predict career satisfaction among practicing psychologists. These researchers identified several predictive algorithms that separate highly satisfied from moderately satisfied psychologists.…”
Section: Understanding Various Types Of Career Satisfaction: Context mentioning
confidence: 99%
“…Poor work-life balance has also been linked to exhaustion among mental health practitioners (Scanlan et al 2013) and feelings of anxiety, stress, and being unsettled (Hill et al 2016). In contrast, maintaining balance in life is related to lower levels of emotional exhaustion (Rupert and Kent 2007), greater career satisfaction (Rupert et al 2012), and lower risk of burnout (Levin et al 2017).…”
Section: Balancementioning
confidence: 99%
“…Mason (2016) suggests that meaning-making can interrupt therapists' experiences of compassion fatigue and burnout. Having a sense of meaning and existential well-being in relation to one's work is associated with lower levels of depression (Eakman 2016), less stress and more social support (Calicchia and Graham 2006), greater career satisfaction (Rupert et al 2012), joy (Pooler et al 2014), and less burnout and fewer psychiatric symptoms (Currier et al 2013). For example, neurology residents and fellows who reported meaning in their work were more likely to experience career satisfaction and be at lower risk for burnout (Levin et al 2017).…”
Section: Spiritualitymentioning
confidence: 99%
“…An initial analysis of the results concerning levels of satisfaction revealed that the study participants presented the lowest level of satisfaction in regard to salary and benefits among all the items assessed. In general, studies among psychologists addressing satisfaction with salary have shown a tendency of high levels of dissatisfaction (Rupert, Miller, Hartman, & Bryant, 2012). In regard to the salary of Brazilin psychologists, which is considered low for the profession (Conselho Federal de Psicologia, 2004), Vasconcelos (2004) states that those working in public healthcare services experience huge inequalities in comparison to other professions.…”
Section: Discussionmentioning
confidence: 99%